PANDANGAN GURU PENDIDIKAN ANAK USIA DINI (PAUD) TERHADAP ENGINEERING - Muchammad Arif Muchlisin (Cross-border, 2022)
The dynamics of Science, Technology, Engineering, Art, and Math (STEAM) learning in Early Childhood Education (PAUD) are still in problem from teachers. Meanwhile, the professional development of early childhood teachers is still far from being effective. Whereas the field of engineering as a STEAM domain has been developed and integrated into the early childhood curriculum. The purpose of this study was to determine the views of early childhood teachers on engineering. The survey study was conducted involving 79 PAUD teachers. Data was collected through an instrument scale that has been created and shared online. Analysis of research data was carried out with descriptive statistics and assisted by SPSS. Then the independent sample t-test was conducted to measure the differentiation of PAUD teachers. The results of the study show that PAUD teachers have a high level of perception about the importance of engineering and perceptions of engineers. However, PAUD teachers have a low level of familiarity with engineering and are faced with many challenges. The implication of this research is the improvement of the PAUD teacher professional development program and the provision of engineering courses for early childhood prospective teachers.